The Impact of Interplanetary Magnetic Field Intensity on the Escape of Heavy Ions from the Martian Magnetotail - Yihui Song; Haoyu Lu; Jinbin Cao; Shibang Li; Xiaoshu Wu; Jianxuan Wang; Nihan Chen; Yasong Ge; Yuchen Cao; Jianing Zhao (The Astrophysical Journal)
The interplanetary magnetic field (IMF) is one of the primary factors influencing the Martian plasma environment. In this study, a multifluid magnetohydrodynamic model is adopted to investigate how variations in IMF affect planetary ion escape, particularly the tailward escape flux. Our results reveal that for nominal IMF direction ( $56^° $ Parker spiral), as IMF intensity increases, the ion escape rate decreases considerably. This reduction is primarily due to the decrease in planetary ion density in the plume and the magnetotail, which is caused by the lower ion production rate through the charge exchange process under high IMF conditions. With high IMF conditions, the dynamo at the bow shock is significantly enhanced, leading to a more severe deceleration of solar wind protons and fewer protons entering the magnetosheath. Consequently, intensified electromagnetic fields create a stronger induced magnetosphere, which shields the Martian ionosphere and atmosphere. Although the enhanced loading process for planetary ions results in higher ion escape velocities, the overall ion escape fluxes decrease due to the significant reduction in planetary ion density.